Precise age and petrology of Silurian-Devonian plutons in the Benjamin River – Charlo area, northern New Brunswick - Pilote, Jean-Luc; Barr, Sandra M.; Wilson, Reginald A.; McClenaghan, Sean; Kamo, Sandra; McNicoll, Vicki J.; Bevier, Mary Lou (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2012)
The Late Silurian Landry Brook and Dickie Brook plutons and Charlo plutonic suite underlie a combined area of approximately 80 km2 in the northeastern part of the Ganderian Tobique-Chaleur tectonostratigraphic belt in northern New Brunswick. The Landry Brook pluton is divided into three units: gabbro to quartz diorite, quartz monzodiorite to monzogranite, and monzogranite. A sample from the quartz monzodiorite unit yielded a U-Pb (zircon) crystallization age of 419.63 ± 0.23 Ma. A granodioritic stock located near the Landry Brook pluton has yielded an age of 400.7 ± 0.4 Ma, indicating that it is a younger unrelated body, herein referred to as the Blue Mountain Granodiorite (new name). The Dickie Brook pluton also consists of three units: leucogabbro to quartz gabbro, diorite to quartz diorite and quartz monzodiorite to monzogranite. Two samples from the monzogranite unit yielded U-Pb (zircon) crystallization ages of 418 ± 1 Ma and 418.1 ± 1.3 Ma. The Charlo plutonic suite is a group of small plutons and dykes, located west of the Dickie Brook and Landry Brook plutons and consists mainly of diabase, quartz monzonite to monzogranite, rhyolite porphyry, and dacite porphyry. Chemical trends indicate that the quartz monzodiorite to monzogranite unit of the Landry Brook pluton, all of the units of the Dickie Brook pluton, and the quartz monzodiorite to monzogranite unit of the Charlo plutonic suite, as well as the volcanic host rocks of the Bryant Point and Benjamin formations, are co-magmatic. They formed following slab break-oﬀ and extension in the waning stages of the Salinic orogeny, which resulted from the collision of Ganderia and Laurentia. In contrast, the dacite porphyry of the Charlo plutonic suite may be cogenetic with the younger Blue Mountain Granodiorite and related to the collision of Avalonia with Laurentia.